EKSISTENSIALISME DAN ABSURDISME DALAM DRAMA KARYA PUTU WIJAYA - Suwandana, Engkin (Jurnal Pena Indonesia, 2016)
This study aims to (1) describe the existential drama Oh, Edan, and Dag Dig Dug works of Putu Wijaya which include: (a) freedom, (b) anxiety, (c) the failure, (d) the futility, (e) death, (2) describe absurdism in drama  Ah, Edan, and Dag Dig Dug by Putu Wijaya which includes: (a) suicide philosophical, (b) the nature of the symbolic,  and  (c) of tragedy and comedy. This study focuses on (1) existentialism in the drama Oh, Edan, and Dag Dig Dug  by  Putu Wijaya which include: (a) freedom, (b) anxiety, (c) the failure, (d) the futility, (e) death and (2) absurdism in drama Ah, Edan, and Dag Dig Dug. This study is qualitative research, using descriptive qualitative research data collection. Descriptive method is a method which seeks to describe a phenomenon, the events that occurred at that time. In this study, descriptive method is used  to describe the concept of existentialism and absurdism. This research data  use  existantialism theory  and absurdism in playwrights  by PutuWijaya. By using the technique with  the  data source in the form of three plays, the relevant data collection technique is a technique read. Reading the drama text data collection activities conducted by member?s attention totally focused on the object. Reading and listening is a set of techniques to obtain valid data followed by activities recorded data. This study concluded five concepts of existentialism and three concepts of absurdism. The results showed that existentialism in the drama Oh, Edan, Dag Dig Dug by Putu Wijaya, looked  in terms of freedom, anxiety, failure, futility, and  death.  Three absurdism concepts  in drama Ah, Edan, Dag Dig Dug  by  Putu Wijaya looked through suicide philosophical, symbolic nature, tragedy and comedy.